Academic Librarians' Technological Readiness: Phenomenographic Study of AI Adoption Barriers - Odhiambo, Okita Dan (Journal of Research in Vocational Education, 2025)
This study investigates Artificial Intelligence in North Eastern Nigerian University Libraries: Librarian Perceptions and Challenges. The study was guided by two objectives, two research questions, and one hypothesis, it employed a descriptive survey design, targeting professional librarians across state and federal universities. Data were collected via a Google Form questionnaire on a 4-point Likert scale, distributed through WhatsApp networks, and analyzed using mean, standard deviation, and Pearson Chi-square tests (SPSS v23.0). Findings reveal a moderate perception of AI’s potential to enhance services, reduce repetitive tasks, and boost productivity, though significant challenges like funding and infrastructure persist. The hypothesis test confirmed that librarians’ perceptions significantly influence library services.